Fulfillment of The Constitutional Rights of Abandoned Children Victims of Economic Exploitation - Nuvazria Achir (Universitas Negeri Gorontalo, 2022)
The existence of abandoned children who are victims of economic exploitation in Gorontalo City is very concerning, because there are many cases related to violence and unfulfilled guarantees of human rights to children. This study aims to find out how to fulfill the constitutional rights of abandoned children as victims of economic exploitation and its inhibiting factors in the city of Gorontalo. The research method uses a case approach and is analyzed qualitatively, data collection through observation, interviews and documentation. The results showed that the fulfillment of children's rights in Gorontalo city was carried out through assessment efforts, cooperation in regional apparatus organizations (OPD), the implementation of raids and interventions, the provision of protection cars (Molin) and mobile motorcycles (Torling) as well as the use of shelter facilities. Factors Hindering the fulfillment of rights include the Economic Difficulties of Parents, Education to children and families has not been sufficiently helpful, because the reasons for carrying out economic activities on their own desires and the demands of needs.